Perceptions of elderly patients with hip fractures and their relatives on their illness and quality of nursing care received in an academic hospital in Gauteng - Skaarnek, Bettie (My University, 2022)
There has been an increase in the number of complaints among orthopaedic patients, including elderly patients with hip fractures with regard to the nursing care received in the public sector hospital in which the study was conducted. The manner in which nursing care is provided has an impact on the how satisfied patients are with the care they received during their hospitalization. The nursing care received by patients also has an influence on how content their relatives are. However, no studies could be found on the perceptions of elderly patients with hip fractures and their relatives on nursing care received, from a South African perspective. The aim of this study was to explore and describe the perceptions of elderly patients with hip fractures and their relatives, on their illness and quality of nursing care received in an academic hospital in Gauteng. This was to gain an understanding on how to enhance the quality of nursing care for elderly patients with hip fractures. The sample size was 5 participants in each phase to explore and describe the perceptions of elderly patients and their relatives to answer the research question. A qualitative, exploratory, descriptive research design was followed. Data was collected through semi-structured interviews, using the total sampling method. Ethical considerations and measures of trustworthiness were taken into consideration. The findings of the study revealed that the majority of participants in both phases perceived the quality of care as good. However, there were also some shocking reports of bad nursing care received. Nurses should be consistently provided with appropriate knowledge and skill in total patient care of the elderly, through in-service training.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022